Benefit–cost analysis of an interprofessional education program within a residential aged care facility in Western Australia. Issue 6 (2nd November 2019) - Nguyen, Kim-Huong; Seaman, Karla; Saunders, Rosemary; Williams, Elly; Harrup-Gregory, Jane; Comans, Tracy
ABSTRACT: Interprofessional education (IPE) programs in residential aged care facilities (RACF) contributes to the care of older adults whilst providing an environment for students to learn and practise in an interprofessional manner. Clinical placements are provided by RACF through funding and support from universities in collaboration with the RACF. Conducting a benefit–cost analysis (BCA) can determine the sustainability of a clinical placement program such as an IPE program but there is limited research reporting the economic aspects of clinical placements even though it is a university and government priority. This study provides a benefit-cost analysis of an interprofessional education program offered by a residential aged care provider in Western Australia. Analysis using a BCA methodology was conducted to provide information about the level and distribution of the costs and benefits from different analytical perspectives over the three-year period of the IPE program. The analysis showed that the program was highly beneficial from an economic efficiency viewpoint, even though it did not present a financial gain for the aged care provider. The benefits accrued mainly to students in terms of increased education and skill, and to residents in terms of health outcomes and quality of life, while the cost was mostly incurred by the care provider. An IPE program in a RACF is a valuable educational learning experience for students and is also socially beneficial for residents and the broader health sector. For IPE programs in aged care to be sustainable, they require the development of collaborative partnerships with external funding.